Formation of human potential of industrial enterprises: model and information technology. (3rd November 2022) - Ivanova, Valentyna; Ivanov, Oleg; Ivanova, Olena
Every enterprise strives to create competitive advantages for ensuring stable positions in a competitive market or creating new market niches without competitors. For that to happen, enterprises need not only to generate innovations, but also to strengthen innovative activity. They must be constantly prepared for changes. This is possible due to the presence of a powerful human potential of the enterprise, which must be formed continuously. It was proven that knowledge is the basis of all components of an employee's human potential. This was taken into account in the offered model for the formation of the human potential of an enterprise. The human potential of an enterprise is formed through appropriate information flows and is supported with the necessary information. Therefore, the information technology is offered which will ensure the implementation of the model of the human potential formation and prevent the rupture of this process.